CFD Simulation of Dust Cloud Formation in Silo - Siti Ilyani, Rani; Jolius, Gimbun; Badhrulhisham, Abdul Aziz (AENSI Publishing, 2014)
Silo feeding process via pneumatic transport pipe will generates the initial turbulence that causes the dispersion of particles in air. This phenomenon is known as dust cloud formation which is likelihood for an explosive atmosphere. Thus, understanding of dust cloud formation in silo is important for safety measures. This paper presents the results of flow field, in terms of mean and root mean square (RMS) velocity of dust cloud in a silo during axial feeding using commercial computational fluid dynamics (CFD) code,Fluent. The influence of grid size, modeling approach and discretization schemes were examined using turbulence model namely renormalization group k-ε (RNG) combined with disperse phase model (DPM) which follows Eulerian-Lagrangian (E-L) approach.The E-L approach treats solid particles as moving points in the computational domain and their movement is tracked as they moved through the gas flow. Two-way coupling effect was considered since the continuous phase flow field is impacted by the discrete phase. The profiles of mean and RMS velocity at five different axial locations Z = 750 mm, 1750 mm, 2750 mm, 3750 mm and 4750 mm were examined to recognized the flow pattern inside silo. Predicted mean and RMS velocity using combination of DPM and RNG turbulence model with various discretization and pressure interpolation schemes were plotted and compared against experimental measurement adopted from literature,showing a plausibly good agreement with second order upwind scheme and standard pressure interpolation scheme. It was found that predicted flow field has a great influence to the silo height. Higher mean velocity in downward direction was predicted in the center region closer to the top of the silo due to gravitational force on the particles.Moreover, it was found that turbulence flow (RMS velocity) is correspondingly increase with increasing the axial positions, indicating that region closer to the feeding inlet favor the initial turbulence formation. This suggests that combination of RNG turbulence model and DPM could be employed in dust cloud formation study.